Three Worlds of Professional and Managerial Staff in France - Thoemmes, Jens (Relations industrielles / Industrial Relations, 2016)
SummaryChanges in the work of professional and managerial staff (PMS, cadres) in France were studied in a research project based on 100 interviews, conducted in seven private and public companies. Through a discourse and correspondence analysis—of a corpus amounting to some 600,000 words—, this study concludes that this particular French employment group can be seen neither as a homogeneous entity, nor as a totally fragmented socio-professional category. Rather, reflecting on working life experiences, it describes three groups that correspond to a horizontal division of professional and managerial staff: the serene, the individualized and the resistant.“Serene” PMS perceive their professional lives as being free of major problems. Their career trajectories go up, leading to senior positions in the organization. Training opportunities are used and personal assessment by supervisors is seen as a favourable orientation. This world is stabilized by law or by collectively negotiated agreements and characterized by autonomy and concern for the common good, which are the basis of their beliefs.“Individualized” PMS consider themselves to be responsible for their own success and to be the architects of their careers. They put in countless hours of service, arriving early in the morning and going home late in the evening. They prioritize work over family and aim to be active in highly competitive markets. The individualized have everything they need to be “happy,” except that work leaves them very little time for their private lives. In addition, these employees fear threats to job security and to their careers.“Resistant” PMS’s working time is measured in hours and minutes. Unpaid overtime is refused. This strict regulation of working time is nevertheless accompanied by a considerable workload. Deadlines are difficult to respect. Manifestations of stress and responsibilities in personnel management lead the resisting employee to a negative view of work. The importance of sociability in and outside of work compensates for the loss of the traditional prestige of these PMS.